Proposed rain fade mitigation technique for Ka band space earth links in tropical climate - M. Saad, Nor Wahida; Ismail, Ahmad Fadzil; Badron, Khairayu; Mohd. Isa, Farah Nadia; Din, Jafri; Tharek, A.R. (2013)
Satellite communication systems a superior capacity. Millimeter wave offers a allocation, involves small-sized antenna experiences less congested spectrum enviro rain posses a crucial intimidation to such satell links especially in tropical region where the severely affect the signal. Rain is the factor that the implementation of higher frequency communications in this region. Time diversity plausible mitigation technique to coun impairments. It is envisioned that the tech requiring extensive auxiliary’s equipment. Th the likely improvement of a future Ka-band Earth link using proposed time diversity ( tropical regions. The analyses relating to prediction of a satellite communication link assimilating TD scheme are also included. The and its associated equations were determin memory capacity requirement of TD. The integrated accordingly at the receiver with attenuation due to rain endured by the propag Index Terms— fade mitigation techniqu tropical regions, satellite communications